UNUSUAL GROWTH OF POLLEN TUBES IN THE OVARY OF QUINCE (Cydonia oblonga Mill.) - Aleksandar Radović; Dragan Nikolić; Radosav Cerović; Dragan Milatović; Boban Đorđević; Gordan Zec (Acta Scientiarum Polonorum: Hortorum Cultus, 2017)
This paper presents the results of a three-year research (2010–2012) of unusual growth of pollen tubes in the ovary in eight cultivars of quince in two pollination variants (self-pollination and open-pollination). Unusual behavior of pollen tubes growth could be seen in all parts of the ovary, and it was most often manifested by larger or smaller branching and the formation of bundle in the ovary, without signs of further penetration of pollen tubes to the ovule. In addition, in a small number of cases, branching of the pollen tubes, as well as bypassing micropyle and forming swellings at the tips of the pollen tube was noticed. There were also the cases where the pollen tube filled embryo sac forming a bundle in it. The occurrence of unusual growth of pollen tubes in the quince ovary was primarily dependent on the genotype and pollination type. This phenomenon was more expressed in open-pollination than in self-pollination variant in all examined cultivars. Leskovacka cultivar was characterized by the highest percentage of unusual growth of pollen tubes in both variants of pollination, as follows: 13.23% (self-pollination) and 15.89% (open-pollination).